Integrating network pharmacology and experimental validation to clarify the anti-hyperuricemia mechanism of cortex phellodendri in mice - Xu, Lieqiang; Cheng, Juanjuan; Lu, Jieyi; Lin, Guoshu; Yu, Qiuxia; Li, Yucui; Chen, Jiannan; Xie, Jianhui; Su, Ziren; Zhou, Qi (Frontiers in Pharmacology, 2022)
Hyperuricemia (HUA), a common metabolic disease, is treated as the second-largest metabolic disease after diabetes in China. Phellodendri Cortex (PC) is one of the most frequently used herbal medicines for treating gout or hyperuricemia. However, its mechanism of anti-hyperuricemia is still unrevealed. Hence, this study aimed to explore the pharmacological mechanisms of PC against HUA using network pharmacology analysis coupled with in vivo experiment validation. Active compounds and potential targets of PC, as well as the potential targets related to HUA, were retrieved from multiple open-source databases. The drug-disease overlapping targets were obtained by Venn diagram analysis and used to construct herb-components-targets (HCT), protein-protein-interaction (PPI), and components-targets-pathways (CTP) networks. The functional enrichment analysis was also performed for further study. Furthermore, a HUA mouse model induced by hypoxanthine (HX) and potassium oxonate (PO) was used for in vivo experiment validation. The results showed that 12 bioactive compounds and 122 drug-disease overlapping targets were gained by matching 415 PC-related targets and 679 HUA-related targets, and berberine was one of the most important compounds with the highest degree value. The core targets of PC for treating HUA are TP53, MAPK8, MAPK3, IL-6, c-JUN, AKT1, XOD, and ABCG2. The KEGG enrichment results showed that the anti-HUA effect of PC mainly involved in the pathways of inflammation and apoptosis, such as PI3K/Akt, TNF, MAPK, TLR, AMPK, NF-κB, NLRP3 signaling pathways. In vivo animal experiments further confirmed the hypouricemic effect of PC in a HUA mouse model, as evidenced by significantly restoring kidney histological deteriorations, considerably reducing the levels of serum uric acid (sUA), creatinine (Cre), and blood urea nitrogen (BUN). Furthermore, the hypouricemic action of PC in vivo may be attributed to its suppression of XOD activity in the liver, not ABCG2 in the kidney. Real-time qPCR (RT-qPCR) and western blot analysis also confirmed the key roles of the hub genes in PC against HUA. In conclusion, PC showed therapeutic effects against hyperuricemia via multi-compounds, multi-targets, and multi-pathways. It possessed anti-hyperuricemic and nephroprotective effects via suppressing XOD activity and reversing the progression of renal injury by exerting anti-inflammatory and anti-apoptotic effects.